Resveratrol inhibits the formation of Staphylococcus aureus biofilms by reducing PIA, eDNA release, and ROS production - He, Jinfei; Cui, Yilong; Liu, Yan; Mao, Jingdong; Dong, Yanxin; Yao, Ruizhi; Yang, Dahan; Fan, Peichao; Xue, Jiangdong (Frontiers in Veterinary Science, 2025)
IntroductionStaphylococcus aureus is a zoonotic pathogen that is difficult to control. Resveratrol (RES) has been shown to have significant antibacterial effects. The present study aimed to investigate the inhibitory effect of RES on the formation of Staphylococcus aureus biofilms and their molecular mechanism.MethodsFirst, the minimum inhibitory concentration and inhibitory action curve of RES against Staphylococcus aureus were obtained through testing. Second, we found that RES can inhibit biofilm formation by reducing the release of polysaccharide intercellular adhesion (PIA) and extracellular DNA (eDNA) from Staphylococcus aureus.ResultsRES treatment significantly reduced the production of reactive oxygen species (ROS) and nicotinamide adenine dinucleotide phosphate (NADPH) in Staphylococcus aureus, indicating that ROS and NADPH are closely related to biofilm formation.ConclusionThis study demonstrates that RES inhibits the formation of Staphylococcus aureus biofilms by reducing PIA, eDNA release, and ROS production, and these results provide new ideas for the clinical application of RES in the treatment of Staphylococcus aureus infection.